UNDERSTANDING FEMINISM AND WOMEN’S MOVEMENT: ACTIVISM & ADVOCACY OF WOMEN’S RIGHTS - Bhatt, Anushree Pratikkumar; Lopes, Berlina Ajinkya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
As India sets its sights on becoming a developed' nation by 2047, empowering women lies at the heart of this challenge. Women empowerment and socio-economic development go hand in hand, as development alone cannot address gender inequalities. Amartya Sen coined the term "missing women" to highlight ongoing gender disparities globally. With women lagging behind on several parameters of well-being, India must adopt key policies to propel the country towards gender parity in socio-economic outcomes. The term “Feminism” was first coined in the 19th century in association with the women’s suffrage movement and it depicted its relevancy that women should have a right to freedom and in 20th century it believed that men and women posses equal rights. It is always a debatable statement that feminism is all about women’s rights, it is about equality regardless of gender. Gender based study and its discrimination which is borne by women is different for each and every chapter varies. The experience of women who is independent depends on her caste, race, culture, religion, ethnicity and most important her physical ability.